2004
DOI: 10.1111/j.1834-7819.2004.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychic and occlusal factors in bruxers

Abstract: Background: The aim of this study was to investigate the existence of associations between bruxism and psychic and occlusal factors. Methods: Participants in this study (n=85) were recruited from the Section of Odontostomatology, Department of Neuroscience, University of Pisa, Italy. They were split into two groups, bruxers (n=34) and non-bruxers (n=51), on the basis of the presence of both clinical and anamnestical indicators of bruxism. All participants were administered two self-reported validated questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
96
4
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 31 publications
12
96
4
14
Order By: Relevance
“…Many practitioners believe that bruxism is caused by psychological stress, but such statements are not strongly evidence based. 4,5 The majority of patients with sleep bruxism represent any associated medical or psychiatric conditions (idiopathic or primary bruxism), while patients with daytime bruxism have been reported to depict basal ganglia infarction, multisystem atrophy, cervical dystonia, or use and deprivation of some drugs (secondary bruxism). 6,7 There are various explanations on the aetiology and pathophysiology of this disorder in literature, but none of them is confirmed or disproved scientifically, yet.…”
Section: Introductionmentioning
confidence: 99%
“…Many practitioners believe that bruxism is caused by psychological stress, but such statements are not strongly evidence based. 4,5 The majority of patients with sleep bruxism represent any associated medical or psychiatric conditions (idiopathic or primary bruxism), while patients with daytime bruxism have been reported to depict basal ganglia infarction, multisystem atrophy, cervical dystonia, or use and deprivation of some drugs (secondary bruxism). 6,7 There are various explanations on the aetiology and pathophysiology of this disorder in literature, but none of them is confirmed or disproved scientifically, yet.…”
Section: Introductionmentioning
confidence: 99%
“…One study estimated that 20% of the population has bruxism during wakefulness and 10% during sleep, occurring most frequently in adolescents and declining with age. Some studies have shown that there is no difference between sexes 3,4 , while others have reported a higher prevalence in women 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…To mogu biti pojedini medicinski poremećaji, poput Parkinsonove i Hantingtonove bolesti, trauma i loših navika. Okidač za bruksizam mogu biti teška zdravstvena stanja kao što su digestivni poremećaji, uznemirenost, neuroze, depresija, hipermiotonija izazvana amfetaminom i lekovima sličnim njemu [3].…”
Section: Etiologijaunclassified
“…To mogu biti pojedini medicinski poremećaji, poput Parkinsonove i Hantingtonove bolesti, trauma i loših navika. Okidač za bruksizam mogu biti teška zdravstvena stanja kao što su digestivni poremećaji, uznemirenost, neuroze, depresija, hipermiotonija izazvana amfetaminom i lekovima sličnim njemu [3].Među navedenim faktorima posebno treba istaći stres, frustraciju, srdžbu i agresivnost, probleme koji prate ži-vot savremenog čoveka. Smatra se da je oko 70% slučajeva bruksizma povezano sa stresom i anksioznošću.…”
unclassified